2002
DOI: 10.1007/s10227-002-1155-5
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Analysis for Microbial Barrier Properties of 2-Octyl Cyanoacrylate-Derived Wound Treatment Films

Abstract: 2-Octyl cyanoacrylate-based films are excellent microbial barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…The two most common complications of circumcision are bleeding and wound infection. [2] The cyanoacrylate tissue glue has been claimed to have the advantages of being hemostatic,[3] bacteriostatic[45] and easy to use.…”
Section: Introductionmentioning
confidence: 99%
“…The two most common complications of circumcision are bleeding and wound infection. [2] The cyanoacrylate tissue glue has been claimed to have the advantages of being hemostatic,[3] bacteriostatic[45] and easy to use.…”
Section: Introductionmentioning
confidence: 99%
“…This makes cyanoacrylate an excellent alternative, not only as suture replacement but also to prevent infection. [15] Cyanoacrylate can also be used in the form of bandages as they have occlusive dressing properties; the rapid hemostatic effect is probably by sealing cuts and leaky vessels. In this regard, Histoacryl, when used as a topical adhesive overapproximated wound edges, is an effective and easily applicable local hemostatic for oral surgery in such patients.…”
Section: Resultsmentioning
confidence: 99%
“…10 In vitro studies have shown that octyl-2-cyanoacrylate is capable of acting as a barrier against infectious organisms, in addition to presenting antibacterial and hemostatic properties. 6,[11][12][13] Borley and Mortensen and Rajimwale and colleagues successfully used octyl-2-cyanoacrylate as a dressing over sutured abdominal and urologic wounds. 14,15 To our knowledge, its use as an occlusive dressing over sutured facial excisions has never been previously reported.…”
Section: Discussionmentioning
confidence: 97%